2011
DOI: 10.2310/jim.0b013e31822a28cd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coronary Angiography and Femoral Arterial Access on Endothelial Functions

Abstract: Coronary angiography did not result in endothelial vasomotor dysfunction. Femoral arterial sheath insertion during coronary angiography was associated with a short-lived endothelial dysfunction. Larger studies are needed to interpret the effect of coronary atherosclerosis on attenuation of endothelial response against arterial wall injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Table 2 summarizes the femoral distensibility and elasticity values, and the comparisons between the groups. coronary angiography alone (13)(14)(15) . In addition, the majority of studies found in the literature focus on the radial artery, so the femoral artery has not been studied in this respect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the femoral distensibility and elasticity values, and the comparisons between the groups. coronary angiography alone (13)(14)(15) . In addition, the majority of studies found in the literature focus on the radial artery, so the femoral artery has not been studied in this respect.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have examined the impact of percutaneous coronary interventions on endothelial function, there are few studies evaluating the effect of coronary angiography alone ( 13 15 ) . In addition, the majority of studies found in the literature focus on the radial artery, so the femoral artery has not been studied in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that cannulation of the arterial system with a sheath during coronary angiography induces temporary endothelial dysfunction [ 11 ]. This endothelial dysfunction leads to arterial spasm due to reduced release of nitric oxide, an endothelium-related vasodilator, and decreased levels of endothelium-related hyperpolarising factor.…”
Section: Discussionmentioning
confidence: 99%